(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In world linguistics, there is always a question of creating terms became relevant and this issue has not lost its importance even today. In this article, linguistic creation principles of a database of English and Uzbek linguistic terms are defined. Every foreign language learner in the process of learning any languages uses dictionaries. Each dictionary belongs to some fields such as linguistic, economic, medical and so on. Additionally, the article is devoted to investigate historical development of lexicography and dictionaries in the English and Uzbek languages. The article describes development of both English and Uzbek language lexicography included into dictionaries. Some methods like observation and comparison is used to reveal differences and similarities of terminology and dictionaries. Much attention is paid to the classification of dictionaries and the characteristics of the main types of dictionaries in English and Uzbek. The structure of dictionaries and entries are analyzed on the material of dictionaries in both languages. English and Uzbek lexicography comparison is carried out at the end of the article. There are also comments on the need for online dictionaries in the Uzbek language. The issue of creating a terminological database (TBD) and the creation of Uzbek online dictionary are illustrated as an urgent task today.